Finding Missing Markets (and a Disturbing Epilogue) : Evidence from an Export Crop Adoption and Marketing Intervention in Kenya - Ashraf, Nava (2012)
Farmers may grow crops for local consumption despite more profitable export options. DrumNet, a Kenyan NGO that helps small farmers adopt and market export crops, conducted a randomized trial to evaluate its impact. DrumNet services increased production of export crops and lowered marketing costs, leading to a 32% income gain for new adopters. The services collapsed one year later when the exporter stopped buying from DrumNet because farmers could not meet new EU production requirements. Farmers sold to other middlemen and defaulted on their loans from DrumNet. Such experiences may explain why farmers are less likely to adopt export crops.